The Effectiveness of Mindmapping in Improving Students’ Writing Skill Viewed from Their IQ - Adi Suyanto (IJEE (Indonesian Journal of English Education), 2015)
This research aims to know whether the mindmapping technique is more effective than the modeling technique in teaching writing, whether the writing skill of the students having high Intelligence Quotient (IQ) is better than that of those having low IQ in learning English, and whether there is an interaction between teaching techniques and students IQ in teaching writing. The research was carried out at SMPN 1 Prambon Nganjuk East Java using experimental method. The subject of the research was each 36 students of the seventh grade 9 and the seventh grade 8. The experimental class used mind-mapping technique and the control class used modeling technique. The data was analyzed by the data using ANOVA or analysis of variance and Tukey test. The findings revealed that: (1) the mind-mapping technique was  effectivein improving students’ writing skill (2) the writing skill of the students having high IQ is better than that of those having low IQ; and (3) there is an interaction between teaching techniques and students’ IQ. Therefore mind-mapping technique is an effective technique to improve the students’ writing skill. Permalink/DOI: http://dx.doi.org/10.15408/ijee.v2i2.3089